Body image in emerging adults: The protective role of self-compassion. (September 2017) - Rodgers, Rachel F.; Franko, Debra L.; Donovan, Elizabeth; Cousineau, Tara; Yates, Kayla; McGowan, Kayla; Cook, Elizabeth; Lowy, Alice S.
Highlights: The direct and indirect protective relationships between self-compassion and appearance esteem were examined in emerging adults. Mindfulness, self-kindness, and common humanity were associated with greater appearance esteem. Mindfulness and common humanity moderated the effect of perceived overweight status on appearance comparison among boys. Self-compassion failed to moderate the effect of appearance comparison on appearance esteem. Abstract: Self-compassion is thought to protect from body image concerns. However, the mechanisms of this effect remain unclear. This study examined three positive dimensions of self-compassion as moderators of the mediated relationship between perceived overweight status, appearance comparison, and appearance esteem. A sample of 232 youth aged 13–18 years, mean = 18.36 ( SD = 1.5) years, reported on appearance esteem, appearance comparison, perceived weight status, and self-compassion dimensions including self-kindness, common humanity, and mindfulness. Among boys, mindfulness and common humanity moderated the perceived weight status to appearance comparison pathway of the mediation ( ps = .01), such that this relationship was weaker among boys with higher levels of these dimensions of self-compassion. These findings were not replicated among girls. None of the self-compassion dimensions moderated the appearance comparison to appearance esteem pathway. Self-compassion dimensions that decrease the focus on the self may protect against body image concerns among boys.